Теоретико-экспериментальный подход при идентификации тепловых процессов в воздушных зонах животноводческих помещений - Слесаренко, А. П.; Романченко, Н. А. (Eastern-European Journal of Enterprise Technologies, 2020)
The theoretic-experimental approach is offered which allows operatively to diagnose and to predict temperature fields in technologically active zones of cattle-breeding industrial premises. For a substantiation of possible differences of temperature between a warmed surface of a floor and air environment above it the simplified model of temperature distribution in a premise which is heated by a warm floor is offered